What is the risk for developing Guillain‐Barré syndrome as a consequence of influenza vaccination?. Issue 8 (August 2016) - Over, Darrell R.; Henson, Gregory
Abstract : Evidence‐Based Answer : There is about a 40% increase in the background rate of Guillain‐Barré syndrome (GBS) after influenza vaccination (SOR: B, meta‐analysis of observational studies). However, the risk of GBS within 6 weeks of an influenza illness may be more than 10 times greater than the risk after influenza vaccination (SOR: C, riskinterval cohort study).